Environmental impact of genetically modified crops - Ferry, Natalie; Gatehouse, A. M. R. (CABI, 2009)
The genetic modification of crops is a subject of intense debate, and opinions are often strongly polarised. This book addresses the major concerns of scientists, policy makers, environmental lobby groups and the general public regarding this controversial issue.